Gleaning from Pro-Poor ICT Experiences to Address Challenges Faced by Uganda’s Nascent Research and Education Network - Kasana, Isaac (My University, 2013)
Research and Education Network for Uganda (RENU), was started by the forum for Vice Chancellors of Universities and heads of Research organisations, in January 2006. In its first seven years it laid an operational foundation covering institutional identity, legal framework, awareness creation, articulating the rationale for national research and education networking (NREN), initial membership development and experimenting with collaboration through formation of the bandwidth consortium, supporting access to library e-resources and related technical skills development for member institutions. However, RENU still faces many challenges to its goal of supporting ICT-enabled research collaboration and higher education transformation to attain WSIS goal No. 3 by 2015 (ITU, 2011). NRENs, like Pro-Poor ICT projects, are mechanisms for addressing a type of ICT access-gap to reduce development lag, so parallels can be drawn between the two mechanisms such as: i. Similar purpose to address development needs through innovative use of ICT. ii. Similar aim to bridge an aspect of ICT access and utilisation gap. iii. Common strategic challenges such as policy environments not conducive to needed interventions and infrastructure costs that are too high for target communities. iv. The need for suitable operational models that enable success and sustainability. In a resource-constrained environment, pro-poor ICT is a rich source of principles, lessons, experiences and best practice that can shape the strategy to move RENU to sustainable operation. Through a desk review of literature, including a study done in 2005(WOUGNET, 2007) on propoor ICT initiatives in Uganda, this paper identifies experiences and lessons that can shape RENU’s plan for addressing its strategic challenges and specify an action framework for becoming fully operational.
Keywords: access-gap; cooperative; sharing-model; competitiveness